Surface broken bonds: An efficient way to assess the surface behaviour of fluorite. (January 2019) - Gao, Zhiyong; Fan, Ruiying; Ralston, John; Sun, Wei; Hu, Yuehua
Highlights: Surface broken bonds can be used to assess surface properties of fluorite. A surface with lower broken bond density shows a high exposure in particles. A surface with higher broken bond density exhibits a faster dissolution. The broken bond method is helpful for mineral/material chemistry research. Abstract: Crushing and grinding, the prerequisite processes in many industries, are employed in areas such as minerals processing and powder technology. During these processes, minerals will cleave or fracture along specific crystal directions, where there are weak inter-planar bonds, generating exposed surfaces. On an exposed mineral surface, different ions can possess different numbers of broken bonds. The total number of broken bonds of all ions on the exposed surface can be considered as the number of broken bonds of the exposed surface. The broken bonds on the exposed surface make the latter more active and determine its reactivity. The broken bond density on the exposed surfaces of fluorite was calculated, enabling the anisotropic surface reactivity of fluorite such as surface energy, surface relaxation, dissolution, wettability, surface charge and adsorbability to be revisited. The results show that the surface broken bond density, which is related to the specific surface energy, could be used to predict the cleavage nature, surface relaxation degree, dissolution rate and surface stability of fluorite crystal. The distribution feature and the number of broken bonds of exposed active ions (such as Ca 2+ for fluorite) can be used to predict and explain the anisotropic surface wettability and surface charge, as well as the adsorption mode and strength of organic molecule binding to different exposed surfaces. The calculation of surface broken bonds can serve as useful method to assess mineral surface chemical behavior. This approach is helpful for mineral/material chemistry research in general.